The Rise of the Dutch Republic $1 (BVolume 12: 1567, part Is - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rise of the Dutch Republic $1 (BVolume 12: 1567, part I" by John Lothrop Motley is a historical account written in the mid-19th century that chronicles the pivotal events surrounding the struggle for independence in the Netherlands during the late 16th century. This work captures the tumultuous climate of a nation on the brink of revolt against Spanish rule, focusing particularly on the religious conflicts and civil strife that marked this historical epoch. The book provides a comprehensive insight into the political dynamics, key figures, and the socio-religious context of the Dutch Republic's rise. In this volume, Motley details the dramatic events of 1567, including the defeat of Calvinist forces at Lannoy and Waterlots and the government$1 (Bs reaction to these incursions, which involved a brutal siege and severe reprisals against the population. Key figures like William of Orange emerge as central protagonists wrestling with their loyalties amid a backdrop of escalating violence. The narrative describes the resilience of the cities under siege, particularly Valenciennes, as well as the fervent debates among leaders as they navigate promises of allegiance and the consequences of impending warfare. Ultimately, the struggle for religious liberty and political autonomy unfolds within the broader context of a nation's fight for freedom, providing a vivid portrayal of this transformative period in Dutch history. (This is an automatically generated summary.)s
Release date is 2004-11-07
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648; Netherlands -- Church history